Evaluation of RBC membrane stabilization and immunostimulatory effect of Sesbania grandiflora flowers extract - Arunabha Mallik; Satish Nayak (International Journal of Phytomedicine, 2014)
To investigate of RBC membrane stabilization and immunostimulatory effect, the effect of Sesbania grandiflora flower extract. Heat induced haemolysis method used for a membrane stabilizing activity and measurement of the IgG and IgM serum levels via enzyme-linked immunosorbent assay used for immunostimulatory activity. In the Investigation, it was observed that methanolic and aqueous extract of Sesbania grandiflora have significant membrane stabilizing activity. At dose of 200 and 400 mg/kg of methanolic extract showed significant increase in the level of IgM and IgG, after four and seven days of the experiment through modulation of B lymphocyte functions. These results suggested that methanolic extracts from Sesbania grandiflora contained several chemical compounds that possess positive modulator effects on the immune system. In summary, these studies provide important insight into the biological activities of Sesbania grandiflora.